(untitled) (Research, Society and Development, 2025)
Pyometra is a common reproductive disease in unspayed female dogs, characterized by the accumulation of purulent exudate inside the uterus. This condition is directly related to the hormonal influence of progesterone during diestrus and to ascending bacterial contamination, with Escherichia coli being the most common agent. This paper aims to report a clinical case of closed pyometra in a twelve-year-old Blue Heeler dog, treated at a veterinary clinic in the municipality of Pimenta Bueno, Rondônia State (RO). The patient presented with apathy, anorexia, vomiting, and increased abdominal volume, symptoms compatible with the closed form of the disease. The diagnosis was confirmed by physical examination, blood count, and abdominal ultrasound, which demonstrated uterine distension and purulent content. After clinical stabilization with fluid therapy and antibiotic therapy, ovariohysterectomy was performed, considered the treatment of choice for the disease. The postoperative period was uneventful, and the animal showed good recovery. This report highlights the need for early detection and emergency surgical treatments, as closed pyometra is a life-threatening condition with a risk of progressing to sepsis and subsequent death. For more severe cases, especially in dogs, routine sterilization is recommended as the most effective method of preventing the disease.